HYDROCEPHALUS WITH VENTRICULOPERITONEAL SHUNTS IN INFANTS: OUR EXPERIENCES AND CLINICAL OUTCOMES - Mandzukovska, Hristina; Sofijanova, Aspazija; Voinovska, Tamara; Timovska, Silvana Naunova; Hristov, Mica Kimovska; Vejseli, Besim; Jordanova, Olivera; Jankovic, Spasija Neskova (Journal of Morphological Sciences; Vol 5 No 3 (2022): JMS, 2022)
Hydrocephalus is a condition resulting from disorder in absorption and circulation of the cerebrospinal fluid (CSF). It leads to progressive ventricular dilatation and need of  ventriculoperitoneal shunt (VP) placement. The aim of our study is to present our experience on neonates with  hydrocephalus, ventriculoperitoneal shunt placement, and early postoperative follow up. A retrospective study on neonates with hydrocephalus borned between January 2019 -January 2022 with ventriculoperitoneal shunt placement conducted at University Clinic for Neurosurgery in Skopje, Macedonia was reviewed. Demographical and clinical characteristics, complications and the need for ventriculoperitoneal shunt were documented. 23 infants with hydrocephalus 14 (60,8 %) were preterm (median birth weight 2120g; mean gestational age 33.1weeks), 9 (39.1%) infants were term neonates (mean birth weight 3600g; mean gestational age 38.4 weeks). The etiology of hydrocephalus were; congenital hydrocephalus in 5 infants (21,7%), prematurity in 6 infants ( 26,08%), spina bifida in 2 infants (8.7%), systemic infection in 4 infants ( 17,3%), and intraventricular haemorrage in 6 infants (26,08%).Ventriculoperitoneal shunt was placed to all 23 infants, at mean age of  33,5 (30-43) days. Postoperative complications as a result of ventriculoperitoneal shunt placement were; ventriculitis was manifested at 3 preterm (13%) infants, 2 of them (8,6%) died. Five term infants (21,7%) with postoperative seizures had need of VP replacement; 2 infants (8,6%) died. 19 infants (82,6%) were discharged and transfed to neonatology department. Ventriculoperitoneal shunt placement is the treatment of choice for neonates with hydrocephalus, although postoperative complications in preterm neonates increase the percent of morbility and  hymortality. Ðšeywords:Hydrocephalus,ventriculoperitoneal shunt, neonates, postoperative complications.